Pocket Primer on the Rheumatic Diseases - Klippel, John H. (Springer London : Imprint: Springer, 2010)
The Pocket Primer on the Rheumatic Diseases is a practical tool for medical professionals caring for patients who have any of the more than 150 rheumatic diseases. This compact text is designed for easy use in the examination room, laboratory, or consultation office. Thorough, yet concise, the Pocket Primer offers the medical professional top-line diagnostic and treatment information for arthritis and other rheumatic diseases. It is fully updated to accompany the new 13th edition of the Primer on the Rheumatic Diseases, one of the most respected and widely used rheumatology textbooks in the world.